Simulations of “tunnelling of the 3rd kind” - Zong-Gang Mou; Paul M. Saffin; Paul Tognarelli; Anders Tranberg (Journal of High Energy Physics, 2017)
Abstract We consider the phenomenon of “tunnelling of the 3rd kind” [1], whereby a magnetic field may traverse a classically impenetrable barrier by pair creation of unimpeded quantum fermions. These propagate through the barrier and generate a magnetic field on the other side. We study this numerically using quantum fermions coupled to a classical Higgs-gauge system, where we set up a magnetic field outside a box shielded by two superconducting barriers. We examine the magnitude of the internal magnetic field, and find agreement with existing perturbative results within a factor of two.